The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/nbt.3055
|View full text |Cite
|
Sign up to set email alerts
|

In vivo interrogation of gene function in the mammalian brain using CRISPR-Cas9

Abstract: Probing gene function in the mammalian brain can be greatly assisted with methods to manipulate the genome of neurons in vivo. The clustered, regularly interspaced, short palindromic repeats (CRISPR)-associated endonuclease (Cas)9 from Streptococcus pyogenes (SpCas9)1 can be used to edit single or multiple genes in replicating eukaryotic cells, resulting in frame-shifting insertion/deletion (indel) mutations and subsequent protein depletion. Here, we delivered SpCas9 and guide RNAs using adeno-associated viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
627
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 693 publications
(671 citation statements)
references
References 41 publications
10
627
0
6
Order By: Relevance
“…Recently, SpCas9 has been proven to be a powerful tool for making precise genomic perturbations in vivo. It has been used in vivo to study the function of genes in the liver and brain [42,43] and to cure metabolic and genetic diseases in animal models [44]. Here, we demonstrated that SpCas9 can be used to disrupt the genes in adult mouse islets.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, SpCas9 has been proven to be a powerful tool for making precise genomic perturbations in vivo. It has been used in vivo to study the function of genes in the liver and brain [42,43] and to cure metabolic and genetic diseases in animal models [44]. Here, we demonstrated that SpCas9 can be used to disrupt the genes in adult mouse islets.…”
Section: Discussionmentioning
confidence: 93%
“…There are two major roadblocks for building these kinds of cellular models. The first one concerns gene editing and, over the past 3 years, has become largely historical: Until recently, genome engineering in human stem cells and neurons has been challenging but transfection of CRISPR plasmids or ribonucleoproteins provides an easy, efficient technique for engineering human cells (Peters et al 2008;Swiech et al 2015). The second major hurdle has been neural differentiation.…”
Section: Bottom-up Approaches Using Exome Sequencing In Autismmentioning
confidence: 99%
“…This powerful technology facilitates targeted DNA double-strand breaks at specific sites in the mammalian genome and takes advantage of the non-homologous end joining (NHEJ) to introduce insertions or deletions (indels). [13][14][15] We demonstrate that miR-10b gene editing is deleterious for all glioma cells and GBM-initiating stem-like cells (GSCs) studied, as their viability strictly depends on miR-10b expression. Furthermore, we show that lentivirus-mediated miR-10b editing with CRISPR-Cas9 strongly impairs the growth of orthotopic GBM in mice, supporting targeted miR-10b gene editing as a promising therapeutic approach for GBM.…”
Section: Introductionmentioning
confidence: 99%